E-lingo newsletter April 2023: issue 1/2023 / Nazima Versay Kudus - Versay Kudus, Nazima (Academy of Language Studies, 2023)
The April 2023 issue of the Universiti Teknologi MARA Cawangan Pulau Pinang (UiTMCPP) e-Lingo Newsletter is dedicated to Mental Health and Emotional Well-Being, a crucial topic that is often overlooked. This 71-page issue, featuring insightful journalism and creative works, serves as a guide for understanding and taking care of one's mental health. The content of the newsletter covers aspects related to this issue, ranging from awareness to symptoms and to treatment. The earlier part of the newsletter features forewords by Advisor Dr. Nur Husna Serip Mohamad, Club President Zawawi Azharuddin, and Chief Editor Erika Clarissa Anak Edwin. Nurul Syahirah Azhar and Muhamad Irfan Ahmad Suhkri's articles shed light on the aspect of awareness in their essays "Mental Health Awareness" and "Connecting Students and Counselors", respectively. Understanding of this issue is also featured in engaging film reviews by Nur Hadirah Md Hadri ("To The Bone") and Nur Adlyn Nazurah Kamsani ("Dead Poets Society"), as well as a song review by Kamalin Mastura Saidin ("Just Hold On" by Presence).